A Mathematical Study on the System of Partial Differential Equations Describing Reverse-Flow Reactor. Issue 4 (3rd July 2016) - Wibowo, Ratno Bagus Edy; Suzuki, Takashi; Takahashi, Ryo
Abstract: The RFR (reverse flow reactor) has been widely studied for abatement of lean methane emission from coal mining or natural gas piping system. We show a global-in-time existence of the solution to a nonlinear system of partial differential equations modeling RFR.